Accompaniment Guide: Brahms’ Scherzo from FAE Sonata - Prommachart, Poom; Rajatanavin, Tanaporn (Rangsit Music Journal, 2025)
Due to the similar resemblance of their ranges, Johannes Brahms’ Scherzo from the FAE Sonata can be performed on both violin and viola. While the differences between the sounds of two string instruments may be hardly noticeable to the untrained ears, piano accompanists must remain adaptable to changes in timbre and other technical aspects when the viola assumes the solo role. This article demonstrates that the shift in instrumentation results in a significantly altered creative outcome, especially when appropriately supported by insightful perspectives on a comprehensive rendition of the piano collaborator. According to music scholars, the viola produces a mellower timbre compared to the violin. Furthermore, the factors such as bow weight, fingerboard spacing, and fingering choices clearly influence how the accompanists would interpret the piece. The historical reviews, of Scherzo from the FAE Sonata, highlight criticisms of Brahms’ writing. The critic has noted that Brahms often placed excessive technical demand on the violin soloist and the instrument itself leading to abrasive effect. The use of viola as an alternative instrument solves this issue due to its resistance to heavy bowing and extreme dynamic contrasts. Moreover, the viola’s rich middle and lower registers enhance the darker tonality of the Scherzo in C minor, offering a more balanced interpretation. The methodology developed from this notion includes exploration of analyses found in key components such as structure, tonality, harmonic activity, motific development, time, and meter among others. The following paragraphs are listed outcomes of such finding. Firstly, the viola line, positioned as an inner voice within the surrounded chordal accompaniment, is being compared to a female Alto voice. The pianist must emphasize this inner line by highlighting the chord tones that are closest to the Alto range making the passage more resonant and attractive. The violin alternative, when play the same opening, is to emphasize the top voice that is closer to the Soprano range instead. Secondly, the issue of fingering can significantly influence how the pianists navigate and accommodates the passages filled with successive intervallic leaps. Since the distances between pitches are greater on the viola due to its longer fingerboard compared to the violin counterpart, players may take more time when shifting positions. In such cases, the pianist must apply acute listening skills to maintain alignment with the soloist, mostly in terms of timing that grants the soloist a form of freedom to express their desired musicality without the restraint of gritty rhythmic units. Thirdly, specific piano techniques play some crucial roles in shaping the piece’s transitions and contrasting melodic models. Absorbed staccato helps smoothen the transitions to avoid any abrupt formal changes that would result in fragmentation of the sections. Applying subtle touches allows for refined control, preventing delicate lyrical passages—rich with harmonic subtleties—from progressing too quickly. These piano techniques encourage prudent pacing that preserves every moment of tranquility, ultimately enhancing the contrast and dramatic impact of the louder sections. The final performance guideline focuses on timbral effects that align with the work’s structure—especially when the viola assumes the role of solo instrument. Performers are advised to refrain from employing exaggerated rubato or abrupt dynamic shift or subito in the retransition or immediately before the main theme’s return in the recapitulation. In this position, the retransition shall not serve as a formal cue but rather an effectuation of timbral changes, thereby enriches the audience’s auditory experience. Subsequently, in the closing five bars of the movement, the rhythmic continuity of tied notes is deliberately interrupted. The severed connection of the chord tones is an adaptation calibrated to the technical requirements of the viola optimizing the instrument’s resonance and coloristic potential at the conclusion. Overall, the primary objective of this article is to emphasize that a well-informed interpretation must be grounded in a thorough understanding of historical and formal contexts—most importantly, a strong grasp of music theory and performance practice. The essential steps for achieving a successful performance, as outlined in this research, encourage musicians and readers to explore alternative interpretations of this work and others of a similar nature. These considerations are made on the notion that performers must remain mindful of their practical constraints that are inherent in unconventional instrumentation, but also explore their unbounded creative possibilities simultaneously. Such an analeptic and reflective approach contributes to development of pedagogical frameworks, offering a flexible process for learning and performing that can be readily applied to comparable works, while fostering critical thinking and listening skills essential for collaborative musicians.